Effect of Bone Morphogenetic Protein-2/Hydroxyapatite on Ankle Fusion with Bone Defect in an Rabbit Animal Model. Issue 3 (14th September 2018) - Lee, Kwang-Bok; Dang, Le Hoang Nam
Category: Basic Sciences/Biologics Introduction/Purpose: Revision arthrodesis surgery after total ankle arthroplasty failure has a problem related with large bone defect management after implant removal. Although autogenous bone is a standard method for the reconstruction of bone defects, it often causes complications such as wound problem, infection, fracture, hematoma, persistent pain and a limited amount of bone.Recombinant human bone morphogenetic protein-2 (rhBMP-2) has a powerful osteoinductive ability, it plays essential roles in bone regeneration strategies. The purpose of this study is to evaluate the substitute ability of rhBMP-2 for autologous bone in rabbit ankle fusion model with distal tibia bone defect. Methods: Bone defect (5 X 5 X 8 mm) was created in the distal tibia between media and lateral malleolus include cartilage. Ankle fusion was performed by 1 cannulated screw from lateral malleolus and various treatments on bone defect. Fifteen male white New Zealand rabbits were divided into three groups of 5 animals on each groups dependent on treatment method; Group I (control, no treatment into defect), II (autogenous bone treatment), III (rhBMP-2/ hydroxyapatite treatment). Bone formation on defect and the union of the ankle joint was evaluated by X-ray, micro-CT scan and histological at 8 weeks and 12 weeks postoperatively. Results: X-ray and micro-CT shows higher bone formation on defect in group II and III than group I at 8 weeks and 12 weeks. According to histological results, completely union between distal tibia and talus in group III, partially union in group II and nonunion in group I. Conclusion: These findings indicate the BMP-2/Hydroxyapatite has a bone fusion effect comparable to autogenous bone, and suggest that rhBMP-2/Hydroxyapatite can be used to substitute for autogenous bone in ankle fusion with a bone defect, thereby overcome the limitations of autogenous bone.